Perancangan Media Promosi Kesehatan Pencegahan Gaki Pada Anak Sd Di Daerah Endemik Di Provinsi Bali - I Putu Suiraoka, Suharyanto Supardi dan Fatwa Sari Tetra Dewi (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Iodine Deficiency Disorders (IDD) is a serious problem in Indonesia. IDD control program was implemented through some preventive action, included iodized salt. Housewives knowledge regarding IDD is a factor that could influence the availability of iodized salt in household. Their knowledge could be improved through knowledge improvement of Primary school children regarding IDD, because they considered as one of message carriers in the household. Health education activity at school was implemented through discourse without using media. Therefore, media is need to make the health education process could run effectively. This research was aimed to design health promotion media that suitable with primary school children in endemic area of IDD in Bali province. Methods: This was a qualitative research that used in-depth interview with subject's teachers, psychologists, education practitioners, and nutrition officers. In addition, this research was also implemented with focus group discussion toward 8 groups of primary school children from two characteristics and Check List of Primary School children response toward media design. Results: Health education problem at primary school children in Karangasem District was media limitation, existence risk of IDD effect, and also social phase of primary school children at concrete operational. The communications strategy in health promotion of IDD prevention consisted by formulated goals, information's, channels and methods. Primary school children (target audience) in this research had a notion that items, channel, media type for them were media with a lot of picture illustration like leaflet, booklet, and pictorial story. Result of pre-testing media indicate that the physical vision from leaflet, booklet, and pictorial story compatible to target specification. The evaluation planning included the process and impact evaluation from health promotion program of IDD prevention at primary school children. Conclusion: According to primary school children, health education at school conducted with the personal communications (discourse). Media type of IDD prevention which primary school children wanted was leaflet, booklet, and pictorial story. Figure of family member as picture illustration in the media will give the reinforcement effect to the massage. Target response to media device was good. Keywords: health promotion media, IDD, primary school children